2020
DOI: 10.1556/1886.2020.00028
|View full text |Cite
|
Sign up to set email alerts
|

ESX secretion system: The gatekeepers of mycobacterial survivability and pathogenesis

Abstract: Mycobacterium tuberculosis, the causative agent of Tuberculosis has plagued humankind for ages and has surfaced stronger than ever with the advent of drug resistance. Mycobacteria are adept at evading the host immune system and establishing infection by engaging host factors and secreting several virulence factors. Hence these secretion systems play a key role in mycobacterial pathogenesis. The type VII secretion system or ESX (early secretory antigenic target (ESAT6) secretion) system is one such crucial syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…The five type VII secretion systems (ESX) of M. tuberculosis secrete specific components into the host and are crucial for M. tuberculosis' virulence (61,62). Deletion of part of the ESX1 system, known as region of difference 1 (RD1), is the basis of the attenuation of the BCG vaccine (63,64).…”
Section: Virulence Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The five type VII secretion systems (ESX) of M. tuberculosis secrete specific components into the host and are crucial for M. tuberculosis' virulence (61,62). Deletion of part of the ESX1 system, known as region of difference 1 (RD1), is the basis of the attenuation of the BCG vaccine (63,64).…”
Section: Virulence Factorsmentioning
confidence: 99%
“…Deletion of part of the ESX1 system, known as region of difference 1 (RD1), is the basis of the attenuation of the BCG vaccine (63,64). Apart from their role in the interactions between M. tuberculosis and its host, the ESX systems are also important for cell wall integrity and may play a role in conjugation (62,65). The RNA-seq data set revealed that the ESX systems 4 and 5 had expression levels in all stress conditions mostly similar to exponential growth (Table S2c).…”
Section: Virulence Factorsmentioning
confidence: 99%
“…As such, the SC-SVM classifier identified Mtb transcriptomes from slow-growing (i.e., dormancy-inducing), but viable conditions. In contrast, the excluded transcriptomes (total 1,940) ( Table S1 ) were from stressful conditions (e.g., drug treated, heat treated, amino acid starved) and lethal genetic perturbations (e.g., phoP , espR , mihF mutants) that reduced cell viability in Mtb cultures ( Foddai et al., 2010 ; Odermatt et al., 2018 ; Pérez et al., 2001 ; Roy et al., 2020 ; Tiwari et al., 2018 ).
Figure 1 Overview schematic of DRonA/MLSynergy framework DRonA is a SC-SVM that was trained on transcriptomes from viable Mtb cultures.
…”
Section: Resultsmentioning
confidence: 99%
“…A notable consequence of these activities is the enhanced detection by cytosolic PRRs. For example, Mycobacterium tuberculosis uses a Type VII Secretion System, termed ESX‐1, to release the membranolytic protein ESAT‐6 (also known as EsxA) into the phagosomal lumen (Roy et al., 2020). ESX‐1 and ESAT‐6 are required for a sub‐population of M .…”
Section: Bacteria‐directed Activities That Promote Pamp Access To Cytosolic Prrsmentioning
confidence: 99%